Model tests of prefabricated horizontal drains with vacuum preloading on clay slurry for land reclamation - Goh, Joel Han (2016)
Land reclamation is a process of creating new land, usually from coastal areas, rivers or lakes by filling it with suitable soil materials. Pioneer reclamation projects in Singapore were carried out at a swampy ground in the area called South Boat Quay in the early 1800s. Singapore has plans to carry out more land reclamation projects to increase the land area by another 10,000 ha beyond 2030. The reclamation projects in Singapore include expansion of the Changi Airport, Pulau Tekong, Jurong Island, etc. Due to the limited supply of fill materials, Singapore has to import the landfill material from other countries such as Cambodia. However, this approach will not be sustainable in the long run due to the increasing cost of landfill materials. Hence in this report, we look into the use of marine clay and clayey soils as an alternative material to the granular soils that are typically used. The usage of clayey soil has its own set of challenges with the fine grained soils presenting a much longer settlement and consolidation time, which could result in potential delay in projects and eventually sustained economic losses. Therefore, in this project we also look into the use of vacuum to accelerate the settlement and consolidation process. This FYP project reports the findings of the technical feasibility of using the chemical flocculant hydrated lime on the consolidation, and vacuum pressure on the settlement and dewatering of clayey soil.